Baohuoside I Inhibits Tumor Angiogenesis in Multiple Myeloma via the Peroxisome Proliferator–Activated Receptor γ/Vascular Endothelial Growth Factor Signaling Pathway - Chen, Ying; Zhang, Lina; Zang, Xiaoyan; Shen, Xuxing; Li, Jianyong; Chen, Lijuan (Frontiers in Pharmacology, 2022)
Angiogenesis plays an important role in the development of multiple myeloma (MM). Baohuoside I (BI) is a core flavonoid monomer with anticancer property. However, the mechanism of BI on MM-stimulated angiogenesis has not been revealed. In this study, we demonstrated that BI inhibits MM-induced angiogenesis in vitro and angiogenesis in a xenograft mouse model in vivo. We further showed that peroxisome proliferator–activated receptor γ (PPARγ) transcriptional activity was mediated by a direct physical association between BI and PPARγ. Meanwhile, inhibition of PPARγ using lentivirus transfection of shRNA in human myeloma cell lines showed that the facilitation of PPARγ blocked angiogenesis and PPARγ repressed vascular endothelial growth factor (VEGF) transcription. Furthermore, BI treatment decreased VEGF expression, whereas VEGF expression remained unchanged after PPARγ knockdown when exposed to BI. Overall, our study is the first to reveal that BI inhibits MM angiogenesis by the PPARγ–VEGF signaling axis.